2004
DOI: 10.1080/13691050410001731116
|View full text |Cite
|
Sign up to set email alerts
|

Precautionary tales: Condom and contraceptive use among young Australian apprentices

Abstract: Condom and contraceptive use at first intercourse have become important reference points in monitoring the sexual health of young people. This study describes the precautionary practices of a national stratified cluster sample of 3133 Australian hairdressing, automotive, and commercial cookery apprentices aged 15 to 24 years. Approximately 77% of the apprentices reported using a condom, the oral contraceptive, spermicide, IUD, or a diaphragm at first intercourse. Of these, 91.7% used a condom either alone or i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…However, the research literature on condom use demonstrates that condoms are often not routinely or consistently used in sexual encounters (e.g. Abel and Brunton, 2005; Adolescent Health Research Group, 2003; de Visser and Smith, 2001; Fisher and Boroditsky, 2000; Grimley and Lee, 1997; Grunseit, 2004; Measor, 2006; Santelli et al., 1997; Tavory and Swidler, 2009; Wellings et al., 2001), even when there is a common understanding of the importance of condom use for sexual health (Mantell et al., 2011; Mashinini and Pelton Cooper, 2012; Williamson et al., 2009), and/or an intention or desire to use them (Gavey and McPhillips, 1999; Gavey et al., 2001). The persistence and even increase in STI incidence is an outcome of inconsistent use.…”
Section: Cultural Narratives Sexually Transmitted Infections and Thementioning
confidence: 99%
“…However, the research literature on condom use demonstrates that condoms are often not routinely or consistently used in sexual encounters (e.g. Abel and Brunton, 2005; Adolescent Health Research Group, 2003; de Visser and Smith, 2001; Fisher and Boroditsky, 2000; Grimley and Lee, 1997; Grunseit, 2004; Measor, 2006; Santelli et al., 1997; Tavory and Swidler, 2009; Wellings et al., 2001), even when there is a common understanding of the importance of condom use for sexual health (Mantell et al., 2011; Mashinini and Pelton Cooper, 2012; Williamson et al., 2009), and/or an intention or desire to use them (Gavey and McPhillips, 1999; Gavey et al., 2001). The persistence and even increase in STI incidence is an outcome of inconsistent use.…”
Section: Cultural Narratives Sexually Transmitted Infections and Thementioning
confidence: 99%
“…Earlier studies found a lower probability of contraception if adolescents were younger at first intercourse and forced or coerced into sex (Grunseit, 2004). Higher socioeconomic status has been shown to be associated with more contraceptive use (e.g., Hogan, Sun, & Cornwell, 2000), probably because students from higher school tracks, with higher educational attainment and from families with better parental education, may have more knowledge about sexual risk factors and better access to contraceptives.…”
Section: Contraceptionmentioning
confidence: 96%
“…Additionally, they describe condom use becoming 'normalised', with an expectation that condoms would be used in early stages of relationships or in casual sex. Grunseit (2004) found that contraceptive use was associated with sex with a regular partner or where sex was planned. Perhaps this more recent work is an indication that attitudes to condom use are changing, particularly as far as their implications for female reputations, and planning to have sex, are concerned.…”
Section: Introductionmentioning
confidence: 99%